Insights Into the Inhibition of MOX-1 β-Lactamase by S02030, a Boronic Acid Transition State Inhibitor - Ishikawa, Tatsuya; Furukawa, Nayuta; Caselli, Emilia; Prati, Fabio; Taracila, Magdalena A.; Bethel, Christopher R.; Ishii, Yoshikazu; Shimizu-Ibuka, Akiko; Bonomo, Robert A. (Frontiers in Microbiology, 2021)
The rise of multidrug resistant (MDR) Gram-negative bacteria has accelerated the development of novel inhibitors of class A and C beta-lactamases. Presently, the search for novel compounds with new mechanisms of action is a clinical and scientific priority. To this end, we determined the 2.13-angstrom resolution crystal structure of S02030, a boronic acid transition state inhibitor (BATSI), bound to MOX-1 beta-lactamase, a plasmid-borne, expanded-spectrum AmpC beta-lactamase (ESAC) and compared this to the previously reported aztreonam (ATM)-bound MOX-1 structure. Superposition of these two complexes shows that S02030 binds in the active-site cavity more deeply than ATM. In contrast, the SO3 interactions and the positional change of the beta-strand amino acids from Lys315 to Asn320 were more prominent in the ATM-bound structure. MICs were performed using a fixed concentration of S02030 (4 micrograms/ml) as a proof of principle. Microbiological evaluation against a laboratory strain of E. coli expressing MOX-1 revealed that MICs against ceftazidime are reduced from 2.0 micrograms/ml to 0.12 micrograms/ml when S02030 is added at a concentration of 4 micrograms/ml. The IC50 and Ki of S02030 vs. MOX-1 were 1.25 ± 0.34 µM and 0.56 ± 0.03 µM, respectively. Monobactams such as ATM can serve as informative templates for design of mechanism-based inhibitors such as S02030 against ESAC beta-lactamases.